The role of accounting in the industrialization efforts of the Ottoman Empire in the 19th century - Güvemli, Batuhan (De Computis, Revista Española de Historia de la Contabilidad., 2017)
When the need for industrialization surfaced in the 19th century, Ottoman Empire aimed to establish state-led, profit-oriented enterprises after the Imperial Edict of 1839, which is also known as Tanzimat. Experienced accountants of the state tried to do the investment calculations of an iron factory in the 1840s (Istanbul) by benefiting from the merdiban accounting method, which was initially developed to record the revenues and expenditures of the state. This study contributes to the relevant literature by analyzing the adequacy of this statist-centralist accounting method within a profit-oriented environment and its role in this failed attempt towards industrialization. Merdiban allows the separation of investments as actual construction, still projected and shows the payment status of investments in details. As one of the first profit oriented investment project in the history of the Ottoman Empire, accountants mislead critical pieces of information like plans for procurement of raw materials, projected sales, payback time, capacity and depreciation. Findings indicate that neither accountants nor the method were ready to operate in a for-profit organization, eventually resulting diminish of this old accounting method in 1879.